CONFIGURING THE ROLE OF THE UNITED NATIONS SECRETARYGENERAL IN THE PEACEFUL SETTLEMENT OF INTERNATIONAL DISPUTES. RELATIONS WITH THE SECURITY COUNCIL AND THE GENERAL ASSEMBLY - OANA-ADRIANA IACOB (Challenges of the Knowledge Society)
In an international context embracing the idealist concepts of harmony, cooperation, structural peace, illegality of war, the United Nations Organization has created a system of peaceful settlement of disputes, based on principles of justice and international law. In this framework, the organs bearing the responsibility of peaceful resolution of conflicts are the International Court of Justice, the Security Council, the General Assembly and the Secretary-General. The latter has a unique position, triggering a spectacular evolution of its role in the maintenance of international peace and security. The challenges of the international environment and the outstanding ways in which they were addressed by the distinctive personalities that filled the function of the Secretary General, creating precedents and influencing its future development, have led to a continuous enlargement of its role. The purpose of the present paper is that of defining the role of the Secretary-General in the system of peaceful settlement of international disputes created by the United Nations, by analysing the relevant provisions consecrated in the Charter and by revealing and explaining the outstanding evolution of this institution, with an emphasis on the relations of mutual influence between the High Official, on one side, the Security Council and the General Assembly, on the other.